Developmental expression and role of kinesin Eg5 during Xenopus laevis embryogenesis - Fernández, Juan Pablo (2013)
Background: The neural crest is a transient multipotent migratory cell population unique to vertebrates. These cells undergo an epithelial-to-mesenchymal transition and migrate extensively through the embryo. They differentiate into numerous diverse derivatives including the peripheral nervous system, melanocytes,and craniofacial cartilages. The development of the neural crest is mediated by complex interactions of multiple signals and transcription factors. The kinesin Eg5 is a plus end–directed microtubule-based motor protein that is essential for bipolar spindle formation during mitosis and meiosis, axon growth, and mammal embryonic development. Results: We analyzed in detail the expression pattern of eg5 and established that it is expressed at the prospective neural fold, in the premigratory and migratory neural crest. Functional analysis revealed that in Xenopus, early embryogenesis eg5 function is required during neural crest induction, specification, and maintenance. eg5 is also required during neural crest migration and for derivatives formation. Moreover, we demonstrated a hierarchical relationship with the Indian Hedgehog signaling pathway. Conclusions: Our results show that eg5 is essential for the specification and maintenance of neural crest progenitors during Xenopus early embryogenesis rather than cell proliferation and survival.